PENGARUH PEMBERIAN CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN ABU BOILER DAN PUPUK FOSFOR TERHADAPPERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Phaseolus radiatus L.) - Reza Rizki; Al Ikhsan Amri; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to know the interaction and get the best dose of compost mixture of oil palm empty fruit bunches with boiler ash and phosphorus fertilizer to the growth and yield of mung bean. This research conducted in UPT area of research farm in Faculty of Agriculture, Riau University from August 2015 until October 2015. This research used a randomized completely design with two factors and three replications. The first factor is the dose of compost mixture of oil palm empty fruit bunches with boiler ash consist of 3 levels (A1= 0 ton/ha, A2= 5 + 1 ton/ha and A3= 10 +0,5 ton/ha). The second factor is the dose of phosphorus fertilizer that consist of 3 levels (B1= 0 kg P2O5/ha, B2= 46 kg P2O5/ha and B3= 92 kg P2O5/ha). Parameters measured were plant height, number of branch, flowering time, number of nodules, plant dry weight, pods number per plant, the percentage of pithy pods per plant, yield per plant and weight of 100 seeds. Data were analyzed statistically using ANOVA and followed with DNMRT at level of 5%. The result showed the interaction between giving compost mixture of oil palm empty fruit bunches with boiler ash and the phosphorus fertilizer increasedplant dry weight, production per clumps sample and weight of 100 seeds.compost mixture of oil palm empty fruit bunches with boiler ash dose 10+ 0,5 ton/ha and phosphorus fertilizer dose 46 and 92 kg P2O5/ha showed the best result in rate of plant height, number of branch, number of nodules, plant dry weight, pods number per plant, weight of 100 seeds and yield per plant, which is the best yield per plant is 11,96 g             (1,99 ton/ha). Keywords: mung been, oil palm empty fruit bunches, boiler ash, phosphorus fertilizer